Designing a Solar Fuel Device: Light-Harvesting Materials and Catalytic Modules for Artificial Leaf - Joya, K. S. (The Nucleus, 2015)
Solar energy driven catalytic water splitting process using efficient light-harvesting system and catalytic materials can be exploited to generate electrons and protons that can be utilized to make clean hydrogen as a simple renewable fuel. This scheme can also be combined with a CO2 reduction module to convert it into nonfossil and easily storable liquid energy carriers. This approach is very appropriate and attractive but the major obstacle in this pursuit is to develop state-of-the art catalytic modules (both for water oxidation and proton/CO2 reduction) and their synergistic interfacing with light-harvesting materials. Recently, there is a tremendous progress in the field of visible light responsive inorganic-oxide semiconductors and water oxidation electrocatalysts, aiming to build up a stand-alone solar to fuel conversion device, â€œThe Artificial Leafâ€. Many molecular catalysts and nanoscale materials functionalized on the photoelectrode surfaces have been investigated to drive solar water oxidation reaction. Here we give a miniature account of the development of structural designs of solar fuel devices, and assembling of solar to chemical energy conversion system.